2015
DOI: 10.1146/annurev-nucl-102313-025420
|View full text |Cite
|
Sign up to set email alerts
|

Topology, Magnetic Field, and Strongly Interacting Matter

Abstract: Gauge theories with compact symmetry groups possess topologically nontrivial configurations of gauge field. This characteristic has dramatic implications for the vacuum structure of quantum chromodynamics (QCD) and for the behavior of QCD plasma, as well as for condensed matter systems with chiral quasi-particles. I review the current status of this problem with an emphasis both on the interplay between chirality and a background magnetic field and on the observable manifestations of topology in heavy-ion coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 185 publications
(215 reference statements)
0
94
0
1
Order By: Relevance
“…-The emergence of the CME, Eq. (30), is due to the axial anomaly in QED sector which couples the vector current J V to the magnetic field B and the axial chemical 6 One should be noticed that the antipartile of a RH-chirality (RH-helicity) massless fermion is of LH-chirality (RHhelicity) potential µ A , see Fig. 9.…”
Section: A Chiral Magnetic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…-The emergence of the CME, Eq. (30), is due to the axial anomaly in QED sector which couples the vector current J V to the magnetic field B and the axial chemical 6 One should be noticed that the antipartile of a RH-chirality (RH-helicity) massless fermion is of LH-chirality (RHhelicity) potential µ A , see Fig. 9.…”
Section: A Chiral Magnetic Effectmentioning
confidence: 99%
“…In this aspect, the present review is complementary to existing excellent reviews, e.g., Refs. [26][27][28][29][30][31] in which more advanced materials can be found.…”
Section: Introductionmentioning
confidence: 99%
“…The recent reviews of these anomalous transports can be found in Refs. [93,[121][122][123][124][125][126].…”
Section: Magnetic-field Induced Anomalous Transports In Heavy-iomentioning
confidence: 99%
“…Recently several experiments in heavy ion collisions have also indicated an abnormal yield of lepton pairs [20,21] and it was conjectured that the effect may be another manifestation of local parity breaking in colliding nuclei [22][23][24][25][26]. This effect would be due to an interplay between topological fluctuations in QCD (see [27,28] and references therein) and MCS electrodynamics.…”
Section: Introductionmentioning
confidence: 99%